Farm water management constraints to indus basin crop production (For presentation at the 1978 Summer Meeting American Society of Agricultural Engineers, Utah State University, June 27-30, 1978) - Earle, Alan C. (Utah State Univ, 1978)
Farmers water management constraints to full crop procution were investigated by an integrated inter-disciplinary survey technique and delineated into four ategories, physical and irrigation, agonomic and economic, knownledge and information and organizational and institutional services received by farmers.